2013
DOI: 10.1590/s0100-204x2013000500004
|View full text |Cite
|
Sign up to set email alerts
|

Baixa temperatura noturna e deficiência hídrica na fotossíntese de cana‑de‑açúcar

Abstract: Resumo -O objetivo deste trabalho foi avaliar as respostas fotossintéticas da cana-de-açúcar aos efeitos simultâneos e isolados de baixa temperatura noturna (TN) e deficiência hídrica (DH). Após 128 dias do plantio, as plantas da cultivar IACSP94-2094 foram submetidas aos tratamentos: controle, sem DH e com TN de 20°C (TN20); com DH e TN de 20°C (DH/TN20); sem DH e com TN de 12°C (TN12); e com DH e TN de 12°C (DH/TN12) por cinco dias. Após o período de tratamento, as plantas foram irrigadas e submetidas à TN d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
10
0
6
Order By: Relevance
“…This result is in agreement with Machado et al (2013) that, when working with Saccharum officinarum L. (sugarcane), verified that the assimilation of CO 2 decreased in the nocturnal period, when the temperatures were low. Rezende et al (2011) found that stomatal opening is considered the main control mechanism in gas exchange by plants.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with Machado et al (2013) that, when working with Saccharum officinarum L. (sugarcane), verified that the assimilation of CO 2 decreased in the nocturnal period, when the temperatures were low. Rezende et al (2011) found that stomatal opening is considered the main control mechanism in gas exchange by plants.…”
Section: Discussionsupporting
confidence: 92%
“…Taking into account plant responses ( Figures 2 – 5 ) and also soil water availability ( Figure 1 ), we may consider that IW represents a slight water deficit whereas LW represents a severe water deficit. In general, the physiological responses to IW and LW treatments reported herein are already known and described in recent papers (Machado et al, 2009, 2013; Ribeiro et al, 2013; Sales et al, 2013). For instance, reductions in stomatal conductance, carboxylation and photochemistry were associated with the inhibition of sugarcane photosynthesis ( Figures 2 , 3 ) and such responses were genotype-dependent.…”
Section: Discussionmentioning
confidence: 78%
“…Then, we may argue that increases in root growth improved soil volume exploration, indicating an important morphological response under marginally reduced water availability. In general, sugarcane performance under water deficit has been evaluated considering only shoot responses (Inman-Bamber and Smith, 2005; Basnayake et al, 2012; Machado et al, 2013; Ribeiro et al, 2013; Santos et al, 2015), even knowing that plants should maximize the uptake of water and nutrient use to tolerate water deficit (Blum, 2005). Our data revealed that IACSP95-5000 presents higher ability than IACSP94-2094 in acquiring soil water at the initial growth stage when plants face reductions in water availability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivars with best performances were RB867515 (210.9 Mg ha -1 ) and RB931011 (200.0 Mg ha -1 ), which produced 24.7 and 18.2% more stalks in comparison to the mean yield of the experiment in 2011-2012 (169.2 Mg ha -1 ). However, in 2012However, in -2013, the most critical cropping season with respect to the water availability in the soil, the cultivar RB962962 (155.6 Mg ha -1 ) produced 33.7 and 10.5% more stalks than the mean TCH of 2012-2013 ) and the overall mean of the experiment (140.8 Mg ha -1 ) ( Figure 2B).…”
Section: Ws Fi Wdmentioning
confidence: 99%